Activity-to-sedentary ratio provides novel insight into mortality reduction among male survivors of cardiovascular disease in the United States: national health and nutrition examination survey, 2007-2014 - Yuanyuan Ding; Jiahao Chen; Mengying Niu; Qi Xiao; Hongqin Zhao; Xudong Pan; Xiaoyan Zhu (BMC, 2023)
Abstract Background Lower physical activity and sedentary behavior have been identified as modifiable risk factors for cardiovascular disease (CVD). However, the quantitative, dose-response association between activity-to-sedentary ratio (ASR) and mortality is unknown. Methods Prospective cohort studies with participants 50 to 80 years that reported the association between recreational physical activity, sedentary behavior, and all-cause mortality were included from the 2007 to 2014 United States National Health and Nutrition Examination Survey (NHANES) and followed through December 31, 2015. Cox or Weibull regression models and restricted cubic splines were used to determine the association between ASR and all-cause mortality. Results Sixty deaths occurred among 498 CVD survivors, with a median of 56 months of follow-up. After accounting for all covariates, CVD survivors with an ASR between 0.21 and 0.57 (hazard ratio [HR], 0.47; 95% confidence interval [CI], 0.25-0.87) and those with an ASR more than 0.57 (HR, 0.40; 95% CI, 0.20-0.81) were at significantly lower risk for mortality than participants with an ASR <  0.21. Moreover, a nonlinear negative association and an L-shaped association were observed for the level of ASR with risk of mortality among CVD survivors (P for nonlinearity = 0.004). What's more, adjusting for covariates, a statistically significant interaction (P for interaction = 0.016) between sex and ASR, an increase of ASR more than and equal to 0.18 was associated with a lower risk of mortality among males (HR, 0.23; 95% CI, 0.12-0.46). Conclusions An negative correlation between ASR and mortality in CVD survivors, especially in males when ASR is more than 0.18. Our novel findings provide further insights into easing the global burden of deaths.